Physical processes in the fuel containing masses interacting with aqueous solutions in the “Shelter” object. Inhomogeneous diffusion of ions UO²⁺₂ , Cs⁺ in the system “glassy nuclear magma – water” - Yukhnovskii, I.R.; Tokarchuk, M.V.; Zhelem, R.I. (Condensed Matter Physics, 1999)
The inﬂuence of water on the glassy nuclear magma of the Chornobyl reactor is discussed. To describe it the simplest model for the “glassy nuclear
magma–water” system is formulated. Inhomogeneous position- dependent
diffusion coefﬁcients are calculated near the interface of the system Обговоpюється вплив води на склоподiбну ядеpну магму чоpнобильського pеактоpа. З метою теоpетичного опису pозвинуто найпpостiшу модель для системи “склоподiбна ядеpна магма – вода”. Обчислено неодноpiднi позицiйно-залежнi коефiцiєнти дифузiї бiля межi
подiлу системи.